Open Data in musikphilologischen Projekten: Herausforderungen, Strategien, Potenziale - Kepper, Johannes; Münzmay, Andreas (DHd2023: Open Humanities, Open Culture)

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne)
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)
Of the many outstanding female philosophers of the European Enlightenment, Emilie Du Châtelet excelled as a physicist, a philosopher, and a mathematician, as well as a Bible critic. She was famous in her lifetime and was not completely forgotten thereafter. Among her admirers, correspondents and friends were the most acknowledged scholars of her time, including Voltaire, Clairault, Maupertuis, Diderot, Helvetius, La Mettrie, Buffon, Christian Wolff, Leonard Euler, and Johann II Bernoulli. Her philosophical work enjoyed high reputation and her opus magnum, the Institutions physiques, was translated into Italian and German and proved her to be an intellectual of European stature. Its defense of living forces and its implied forecast into dynamics as well as her methodological grounding of scientific knowledge as hypothetical, impacted philosophy and science. Reality must by nature escape us. What we perceive are phenomena. Du Châtelet explains the function of space and time to trace us back to the origin of phenomena. Her influence on Kant is evident. Next to her writings in physics, mathematics, philosophy, language, and logic, she contributed to morality and ethics. Du Châtelet left an opus of quite systematic breadth. This impressive publishing activity excels in the amount of its scientific and philosophical production to which a vast collection of manuscripts must be added.She argued against prejudice and idolatry in philosophy and science. Science is a cooperative undertaking over history and beyond nations. Her moral writings align with ideas of the French materialists. Du Châtelet translated and commented on Newton’s Principia, preparing thus the fertile soil of the generation of physicists to come in France.
Keywords: aura Bassi Luise Gottsched Immanuel Kant Dourtous de Mairan Johann II Bernoulli Algarotti Buffon d’Alembert La Mettrie Principle of contradiction Hypotheses Enlightenment Leibniz-Clarke Correspondence Living forces Dead forces; happiness Space Imaginary beings Monads Epicurus Ethics Women philosophers Newton’s laws Principia Motion inertia Active force Vis viva Vis mortua Hypothetic reasoning Hypotheses; a priori principles; Experience; Dead forces; Living forces; Energy Dynamics

Women in Early Modern Philosophy and Science: An Introduction - Hagengruber, Ruth Edith (Encyclopedia of Early Modern Philosophy and the Sciences)
Essential ideas significantly connected to humanism, Renaissance, and early modern philosophy stem from women’s pens. The supportive role of women in the early modern period has hardly been recognized up to today. The relevant issues women have contributed to range from commentaries on and critiques of the Bible, and their demands for equality and the critique of political institutions, topics that became eminent enhancers of political and societal change in the relevant period of early modern philosophy, to enlightenment philosophy.

Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation

Brückenschläge zwischen Musikwissenschaft und Informatik – Vorbemerkung - Münzmay, Andreas; Aquavella-Rauch, Stefanie; Veit, Joachim (Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation)

NFDI4Culture - Consortium for research data on material and immaterial cultural heritage - Altenhöner, Reinhard; Blümel, Ina; Boehm, Franziska; Bove, Jens; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Dieckmann, Lisa; Effinger, Maria; Hagener, Malte; Hammes, Andrea; Heller, Lambert; et al. (Research Ideas and Outcomes)
Digital data on tangible and intangible cultural assets is an essential part of daily life, communication and experience. It has a lasting influence on the perception of cultural identity as well as on the interactions between research, the cultural economy and society. Throughout the last three decades, many cultural heritage institutions have contributed a wealth of digital representations of cultural assets (2D digital reproductions of paintings, sheet music, 3D digital models of sculptures, monuments, rooms, buildings), audio-visual data (music, film, stage performances), and procedural research data such as encoding and annotation formats. The long-term preservation and FAIR availability of research data from the cultural heritage domain is fundamentally important, not only for future academic success in the humanities but also for the cultural identity of individuals and society as a whole. Up to now, no coordinated effort for professional research data management on a national level exists in Germany. NFDI4Culture aims to fill this gap and create a user-centered, research-driven infrastructure that will cover a broad range of research domains from musicology, art history and architecture to performance, theatre, film, and media studies. The research landscape addressed by the consortium is characterized by strong institutional differentiation. Research units in the consortium's community of interest comprise university institutes, art colleges, academies, galleries, libraries, archives and museums. This diverse landscape is also characterized by an abundance of research objects, methodologies and a great potential for data-driven research. In a unique effort carried out by the applicant and co-applicants of this proposal and ten academic societies, this community is interconnected for the first time through a federated approach that is ideally suited to the needs of the participating researchers. To promote collaboration within the NFDI, to share knowledge and technology and to provide extensive support for its users have been the guiding principles of the consortium from the beginning and will be at the heart of all workflows and decision-making processes. Thanks to these principles, NFDI4Culture has gathered strong support ranging from individual researchers to high-level cultural heritage organizations such as the UNESCO, the International Council of Museums, the Open Knowledge Foundation and Wikimedia. On this basis, NFDI4Culture will take innovative measures that promote a cultural change towards a more reflective and sustainable handling of research data and at the same time boost qualification and professionalization in data-driven research in the domain of cultural heritage. This will create a long-lasting impact on science, cultural economy and society as a whole.
Keywords: Research Data Management

Phonographischer Text, Interpretation und Aufführungsmaterial als kritisch edierbarer Sachzusammenhang. Ein Beitrag zur Theorie der Edition von Klangdokumenten - Münzmay, Andreas; Siegert, Christine (Editio: Internationales Jahrbuch für Editionswissenschaft)
The article discusses possibilities and specific problems of including audio material in the realm of scholarly music editions. From this perspective, the authors propose to include the sounding manifestation of music both into the notion of the musical ‚work‘ and of the musical ‚text‘. The outcome of this thought experiment which considers music as performative art, Beethoven’s and other classical composers’ own wider notions of musical works as musical practice, phonographic recordings as text, different types of music as different types of data, programmed concordances as specific feature of digital editions, and musical interpreters as authors of musical interpretations is a theoretical model that for the first time makes record productions the object of scholarly critical edition.
Keywords: Musikedition; Interpretatsionsforschung; Clifford Curzon

Analysing Constructional Change: Linguistic Annotation and Sources of Uncertainty - Merten, Marie-Luis; Seemann, Nina (Proceedings of the 6th International Conference on Technological Ecosystems for Enhancing Multiculturality (TEEM'18))
This paper presents the various sources of uncertainty we encounter in our project. Our research focus lies on the investigation of language elaboration processes in Middle Low German. We are particularly interested in diachronic constructional changes and constructionalizations involving and affecting all linguistic dimensions. For this, it is necessary to annotate our corpus with Part-of-Speech and constructional tags. Here, we are confronted with gradualness, gradience, and ambiguity as potential sources of uncertainty that complicate the annotation process. Furthermore, due to the historicity of the investigated language, we expect cases of incomplete knowledge and comparative fallacy from the annotators. For this reason, we develop an interface that captures all annotators’ doubts.
Keywords: historical languages; linguistic annotations; gradience and gradualness; ambiguity; incomplete knowledge

Der FID Musikwissenschaft (Musiconn) in Lehre und Forschung. Kommentar aus Nutzer-Perspektive - Münzmay, Andreas (Zeitschrift für Bibliothekswesen und Bibliographie (ZfBB))
Keywords: Library and Information Sciences

Lesen und Schreiben im digitalen Dickicht. Musikwissenschaft, Digital Humanities und die hybride Musikbibliothek - Münzmay, Andreas (Bibliothek: Forschung und Praxis)
Digitalisierung generiert ‚hybride‘ Objekte, die zwar als digitale Datei lesbar und manipulierbar sind, das zugrundeliegende kulturhistorische Objekt jedoch weiterhin ‚enthalten‘. Eine Bibliothek, die Objekte aus ihren Beständen digitalisiert, begründet also eigentlich keine sog. digitale Bibliothek, sondern eine hybride Bibliothek. Im Falle musikalischer Überlieferung ist die Sachlage aufgrund der medienhistorischen Komplexität musikalischer Artefakte besonders unübersichtlich. Verschärft wird die heutige Situation noch durch die Erzeugnisse der Digital Humanities, die keineswegs bloß ‚Informationen‘ sind, sondern ihrerseits komplexe und in der Regel hybride Textgebilde, die häufig komplette digitalisierte Re-Publikationen von Kulturobjekten einbinden, die digital ‚beschriftet‘ und vernetzt werden. Das digitale ‚Dickicht‘ erfordert einen gleichsam genetischen und relationalen Katalog, in dem die konkreten kulturhistorischen Objekte in ihren konkreten Sammlungskontexten – also als Unikate – Ankerfunktion haben. Der Essay geht zurück auf einen Vortrag bei der AIBM-Jahrestagung, Symposium der AG Musikabteilungen an wissenschaftlichen Bibliotheken, Detmold, 8. September 2016.

Annotation Challenges for Reconstructing the Structural Elaboration of Middle Low German - Seemann, Nina; Merten, Marie-Luis; Geierhos, Michaela; Tophinke, Doris; Hüllermeier, Eyke (Proceedings of the Joint SIGHUM Workshop on Computational Linguistics for Cultural Heritage, Social Sciences, Humanities and Literature)
In this paper, we present the annotation challenges we have encountered when working on a historical language that was undergoing elaboration processes. We especially focus on syntactic ambiguity and gradience in Middle Low German, which causes uncertainty to some extent. Since current annotation tools consider construction contexts and the dynamics of the grammaticalization only partially, we plan to extend CorA – a web-based annotation tool for historical and other non-standard language data – to capture elaboration phenomena and annotator unsureness. Moreover, we seek to interactively learn morphological as well as syntactic annotations.

Digitalität in der Musikwissenschaft (Musiktheorie. Zeitschrift für Musikwissenschaft)
Sechs Autorinnen und Autoren widmeten sich für das vorliegende Musiktheorie- Heft aus unterschiedlichsten Blickwinkeln dem Themenfeld der ›Digitalität in der Musikwissenschaft‹. Die Schwierigkeiten eines solchen Unterfangens beginnen im Grunde bei ungeklärten Fragen größeren Maßstabes wie etwa bei der Frage, was genau ›Digitalität‹ sein könnte (ein Textualitätsphänomen, eine spezifische Medialität, eine Methode, noch etwas ganz anderes, oder alles zugleich?) oder bei der Frage nach der Geschichte und Entwicklung von Digitalität (wann begann Digitalität, gibt es überhaupt eine Digitalität oder nicht vielmehr viele ›Digitalitäten‹, wie bedingen und durchdringen sich diese?) oder auch bei der Methodenfrage, wie Digitalität überhaupt beobachtet werden könnte (wären etwa rein ›konventionelle‹ Ansätze in Bezug auf digitale Sachverhalte überhaupt möglich, oder ist Digitales a priori nur mit digitalen Methodenschritten zugänglich?). Solchen Aporien zum Trotz haben die Autorinnen und Autoren sich bereitgefunden, Erkundungen und Vermessungen jeweils bestimmter Regionen dieses weiten Feldes zu versuchen: Thematisiert werden die historisch gewachsene Datenformate-Vielfalt aus dem Bereich Computermusik und Musikinformatik (Albert Gräf) und das durch Jahrzehnte hindurch fortentwickelte methodische Spektrum computergestützter Analyse (Nico Schüler) ebenso wie die Sicht zeitgenössischer Komponisten auf ihre eigenen digitalen Arbeitsumgebungen (Marcus Erbe), die theoretischen und pragmatischen Positionen der aktuellen Digitalen Musikedition (Johannes Kepper und Laurent Pugin) sowie die mit digitalen Daten verbundenen Globalisierungspotenziale im Bereich der ethnologischen Musikforschung (Judith Haug). Der Blick geht dabei jeweils vom eigenen disziplinären Standpunkt beziehungsweise von den jeweils im eigenen fachlichen Bereich vornehmlich anfallenden Datensorten und den jeweils gängigen digitalen Methodiken aus.